GROWTH, NODULATION, PHYSIOLOGICAL INDICES AND YIELD OF SOYBEAN AS INFLUENCED BY SULPHUR AND BORON NUTRITION - J. LAYEK,; B. G. SHIVAKUMAR,; D. S. RANA,; B. GANGAIAH,; K. LAKSHMAN,; B. PARAMANIK, (The Bioscan, 2014)
A field experiment was carried out on alluvial sandy loam soil during 2007-08 at the Indian Agricultural Research Institute, New Delhi to to study the effect of levels of sulphur (S) and boron (B) individually and in combination on the performance of soybean. The treatments consisted of 5 levels of S viz. 0, 10, 20, 30 and 40 kg S/ha and 4 levels of B viz. 0, 0.5. 1.0 and 1.5 kg B/ha. There was significant effect of levels of S and B on the performance of soybean. Application of S upto 30 kg recorded significantly higher growth parameters viz. plant height(57.62 cm), drymatter accumulation(36.66 g/plant), number of branches(3.10), leaf area index(2.89)etc. and yield attributes viz. number of pods/plant(72.00), seed/pod(2.49), seed index(9.99 g)etc. and yield of soybean(1.73 t/ha) as compared to lower levels of S. Similarly application of B@1.0 kg recorded significantly higher growth parameters viz. plant height (57.23 cm), drymatter accumulation (36.37 g/plant), number of branches/plant (3.11), leaf area index (2.70) etc. and yield attributes viz. number of pods/plant (70.47), seed/pod (2.52), seed index (9.79) etc. and yield of soybean (1.75 t/ha). Further increase in thelevels of S and B did not improve the parameters significantly. The combined application of 30 kg S and 1.0 kg B too recorded significant interaction effect on many of the growth and yield attributes and yield of soybean (1.88 t/ha). On the basis of the findings of this experiment it may concluded that there is a need for application of sulphur and boron for improving the productivity of soybean. And a combination of 30 kg S and 1.0 kg B/ha could be sufficient for realizing higher yield from the kharif soybean in the agro-climatic conditions of the Northern Plain Zone of the country